Customer engagement effect on relationship quality through customer co-creation - Akram Gumi; Astri Yuza Sari (Marketing Management Studies, 2022)
This study aims to analyze the influence of customer engagement on relationship quality through customer engagement at the Gaprusy Bukittinggi bag shop. The population in this study are all customers or customers who have shopped at the Gaprusy bag store whose number is not known for certain. While the number of samples in this study amounted to 100 respondents with the characteristics of having shopped in the last 3 months and using the purposive sampling method. The analytical technique used is SEM analysis using smart PLS4. The results of this study are (1) There is a significant and positive influence between customer engagement on relationship quality. (2) There is a significant and positive effect between customer engagement on customer co-creation. (3) There is a significant and positive influence between customer co-creation on relationship quality. (4) Customer co-creation is able to provide a positive mediating role on customer engagement on relationship quality.